2023
DOI: 10.3390/cancers15061835
|View full text |Cite
|
Sign up to set email alerts
|

Is Pediatric Melanoma Really That Different from Adult Melanoma? A Multicenter Epidemiological, Clinical and Dermoscopic Study

Abstract: Purpose: To improve the diagnostic accuracy and optimal management of pediatric melanomas. Methods: We conducted a retrospective descriptive, multicenter study of the epidemiological, clinical, and dermoscopic characteristics of histopathologically proven melanomas diagnosed in patients less than 18 years old. Data on sociodemographic variables, clinical and dermoscopic characteristics, histopathology, local extension, therapy and follow-up, lymph node staging, and outcome were collected from the databases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Furthermore, the youngest group of adult patients (18–30 years) showed a dermoscopic similarity of melanomas with the patients described by Carrera et al regarding the pediatric population—a spitzoid (pigmented or non-pigmented) and non-spitzoid (predominant multicomponent asymmetric) pattern [ 38 ]. Recently, De Giorgi et al indicated a new finding—that pediatric melanomas were predominantly pigmented (95% of their cases) and characterized by at least two melanoma-specific structures in dermoscopy, among which the streaks and pseudopods (typical for the spitzoid pattern) were the most commonly found [ 39 ]. This could be explained by recent data, which indicated that genetic, rather than UV-induced, factors are responsible for the evolution of spitzoid lesions (Spitz/Reed nevi, spitzoid melanoma, and atypical spitzoid tumours) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the youngest group of adult patients (18–30 years) showed a dermoscopic similarity of melanomas with the patients described by Carrera et al regarding the pediatric population—a spitzoid (pigmented or non-pigmented) and non-spitzoid (predominant multicomponent asymmetric) pattern [ 38 ]. Recently, De Giorgi et al indicated a new finding—that pediatric melanomas were predominantly pigmented (95% of their cases) and characterized by at least two melanoma-specific structures in dermoscopy, among which the streaks and pseudopods (typical for the spitzoid pattern) were the most commonly found [ 39 ]. This could be explained by recent data, which indicated that genetic, rather than UV-induced, factors are responsible for the evolution of spitzoid lesions (Spitz/Reed nevi, spitzoid melanoma, and atypical spitzoid tumours) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed a comprehensive analysis of pediatric melanoma cases as well. 2 One particularly noteworthy observation was a significant disparity in mean Breslow thickness between two distinct age cohorts: children aged 0-12 years and adolescents aged 13-18 years. Specifically, the younger age group exhibited a mean thickness of 2.02 mm, whereas the older age group demonstrated a markedly lesser thickness, 0.77 mm.…”
mentioning
confidence: 99%